C-reactive protein: what to expect after bony hip surgery for nonambulatory children and adolescents with cerebral palsy. Issue 4 (July 2019) - Dick, Alastair G.; Magill, Nicholas; White, Thomas C.H.; Kokkinakis, Michail; Norman-Taylor, Fabian
Abstract : Bony hip reconstruction surgery in children with severe cerebral palsy is associated with high complication rates, usually postoperative chest and urinary tract infections. C-reactive protein (CRP) level is commonly used as an indication of infection; an understanding of its normal postoperative trends is crucial to allow early identification of abnormal levels and possible infection. Our aim was to describe the trends in CRP following bony hip surgery in children who had an uneventful postoperative course, on the basis that the children for whom CRP does not follow this course are likely to have a bacterial infection. A retrospective review was performed of 155 children with CP having bony hip surgery between 2012 and 2016. The median age was 9.9 years (interquartile range: 6.6–12.7). One hundred (64.5%) patients had a Gross Motor Function Classification System rating of V. All CRP levels measured in routine postoperative care were recorded, and medical records were examined for postoperative infective complications. The CRP levels of patients with clinically proven infections were excluded in order to describe what to expect in the absence of infection. Mean CRP peaked on the third postoperative day at 81 mg/l in those who had no postoperative infection. Twenty-five (16.1%) patients had a postoperative infection; their mean CRP was higher on all postoperative days and peaked at 128 mg/l on the third postoperative day. An understanding of the normal postoperative trends in CRP allows identification of those with abnormally raised levels. Postoperative CRP is consistently higher in children with an infective complication. We recommend that the CRP should be routinely checked following bony hip surgery in children with CP, and a careful search for infection undertaken in those with a raised level.